Christianity and power: an ancient misconception - Lino, Brissos (2020)
The history of civilizations is largely tied to the religious domain in its most diverse forms. From the most explicit to the most subtle, from the days of Constantine to the present day, from the West to the East and involving practically all expressions and branches of the Christian faith. This domain is verified in terms of content as well as form. This thirst for power in both appearance and substance clearly shows how the essence of the Gospel was not properly assimilated by Christians throughout History, or at least was not more important than acquiring power in ancient times, whether through self-defense or as Camões would put it: “the vain glory of ruling.”